(untitled) (Socio-economic relations in the digital society, 2019)
This article considers and investigates key aspects, features and recording in accounting process, impairment of assets in accordance with international standards, comparing NAS 28 «Impairment of Assets» and IAS 36 «Impairment of Assets», results of this are identifi cation certain differences and similarities between these standards. In this article also considered problems and disadvantages of Ukrainian system of standards comparing with international standards and given suggestions how to achieve level of other countries in accounting of process of impairment of assets. Also practical examples of proper valuation of assets and process of impairment of assetsare shown.